(untitled) (University Arena, 2025)
For practicing Tae Bo will not be sufficient to perform a number of training sessions a week, in which to sweat or burn many calories. This discipline requires, more than any other, equal participation of our psyche during training. To achieve assimilation proper technique should always think about what we do to that Tae Bo is not a contact sport but a fight - with an imaginary opponent, a battle with ourselves, to be a dispute at a highest level of technical. Tae Bo is an exercise program that combines the best of several different disciplines. A combination of martial arts, boxing, aerobics and dance exercises posted on a trained musical background, here’s the secret world of this new trend in exercise. The exercise is relatively easy and convenient for anyone who wants to do maintenance but the move may be designed workouts for weight loss or development and driving qualities.